A weighted extremal function and equilibrium measure - Bos, Len; Levenberg, Norman; Ma’u, Sione; Piazzon, Federico (MATHEMATICA SCANDINAVICA, 2017)
We find an explicit formula for the weighted extremal function of R^nC^n with weight (1+x_1^2+… +x_n^2)^-1/2 as well as its Monge-Ampère measure. As a corollary, we compute the Alexander capacity of RP^n.